Model Jaringan Irigasi Tetes Berbasis Bahan Lokal untuk Pertanian Lahan Sempit - Dadang Ridwan (Balai Teknik Irigasi, 2013)
The existence of a broad decline in land ownership,model of drip irrigation network with local material based is expected to be appropriate technologies model for farmers especially to optimize the utilization of small land for agriculture. The objective of this research was to develop drip-irrigation network based on local material, with low investment cost, easy implementation and had a good performance. The research was carried out using experimental method. The research was conducted at the Outdoor Laboratory of Experimental Station for Irrigation. The result of study showed that the network model has a good performance with distribution uniformity (DU) value 85.88%, and much cheaper (around 56.70% ) than fabricated of drip irrigation with standard materials. A side that implementation of this irrigation network model was feasible, and potential for small land use with less than 1000 m2, with the pattern of irrigation operations is in turn per each irrigation blocks.